2017
DOI: 10.1002/ijgo.12395
|View full text |Cite
|
Sign up to set email alerts
|

Predicting success of methotrexate treatment by pretreatment HCG level and 24‐hour HCG increment

Abstract: A β-HCG increment of less than 14% in the 24 hours before single-dose methotrexate and serum β-HCG of less than 1600 IU\L were found to be good predictors of treatment success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…This might explain why the authors have found that early β-hCG kinetics does not adequately predict treatment outcome and that initial serum β-hCG measurement was the only significant prognostic factor for MTX efficacy-this in contrast to recent literature that early β-hCG kinetics is indeed an early determinant of treatment success but the β-hCG level itself on day 1 is of no predictive value [4]. At Last, if an early predictors are on the spotlight, it should be acknowledged that earlier predictors have been studied and found to be predictive for MTX treatment success such as pretreatment β-hCG kinetics [4,5].…”
Section: Dear Editorsmentioning
confidence: 77%
“…This might explain why the authors have found that early β-hCG kinetics does not adequately predict treatment outcome and that initial serum β-hCG measurement was the only significant prognostic factor for MTX efficacy-this in contrast to recent literature that early β-hCG kinetics is indeed an early determinant of treatment success but the β-hCG level itself on day 1 is of no predictive value [4]. At Last, if an early predictors are on the spotlight, it should be acknowledged that earlier predictors have been studied and found to be predictive for MTX treatment success such as pretreatment β-hCG kinetics [4,5].…”
Section: Dear Editorsmentioning
confidence: 77%
“…Importantly, our study showed that % HCG change per day is a predictor of both single‐ and second‐dose successful MTX treatments. Interestingly, we did not regard requiring a second administration of MTX as treatment failure, while previous studies made this categorization . The major benefit of MTX treatment would be the avoidance of surgical intervention, and for that purpose, the second dose of MTX is acceptable.…”
Section: Discussionmentioning
confidence: 96%
“…da Costa Soares et al and Cohen et al reported lower increases in the 48 hours before treatment as a predictor of success with a cutoff value of 11.1% and 12%, respectively. In a recent study of 69 patients, Levin et al found that HCG increases of <14% in the 24 hours prior to treatment were also strong predictor. Importantly, our study showed that % HCG change per day is a predictor of both single‐ and second‐dose successful MTX treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have nicely stated that that an earlier indicator of treatment efficacy would reduce patient anxiety. Early diagnosis and treatment decisions are of paramount importance, and every effort should be made to comply with this statement, and studies have been performed in light of this concept . Therefore, it should be also emphasized that 35.9% (28/78) of all successfully treated patients did not experience an early drop of serum hCG levels, and would have received a false early prediction of treatment failure—with associated anxiety and reduced hope.…”
mentioning
confidence: 99%